Building Community Literature Interest Through the Perpusjal Program in Jatirokeh Village, Songgom District, Brebes Regency - Annur , Aan Fadia; Saidi, M. Arfan; Musa, Muhammad Maskur (Amala Jurnal Pengabdian Kepada Masyarakat, 2023)
Literacy is a vital talent in life because it includes individual talents and competencies in reading, writing, speaking, calculating, and solving problems. Literacy is closely related to language skills. Roughly, literacy can also be interpreted as reading and writing, which is also the basis for achieving a higher level of literacy skills and abilities that are useful in everyday life. The case of the COVID pandemic, which stopped the activities of the entire community, was no exception to the teaching and learning process in schools, which resulted in an online system and activities at home. Judging from the observations of the current situation and conditions, there are many children and teenagers in the Jatirokeh area where online learning is considered less than optimal for educating character. This study aims to provide awareness and build interest in reading for residents during the COVID-19 pandemic, especially in Jatirokeh Village, Songgom District, and Brebes Regency. This service method uses several methods, including: 1) Opening communication with parties that allow for book donations 2) Collecting books from donations from various parties 3) Holding a Street Library (PERPUSJAL) 4) Holding "Ngabuburead" activities during the month of Ramadan. The subject of this research is local residents and youth in Jatirokeh Village, Songgom District, Brebes Regency. Data collection was obtained using library techniques, followed by data processing techniques using data analysis. And for the interpretation of data, interpret in the form of a description so as to get good data. Efforts are being made to build and increase awareness of people's interest in reading by providing reading facilities, visiting people's places, and organizing interesting activity programs.